Hospital, suffering, psychology: intercepting demands. - Civitillo, Andrea (Rivista di Psicologia Clinica, 2013)
What problems does psychology meet in Hospital, how can it intervene? How can it deal with healthcare culture demands? This paper aims to contribute to such matters by proposing an intervention method based on some psychological clinical models focused on relationship. The context is the Unit of Psychology of a Hospital in Rome, in which the author works as trainee. The paper introduce some possible psychological clinical interventions that deal with cancer patients’ suffering, the problems of the healthcare work team in the Cancer Ward, the demands addressed to the Unit of Psychology and its offer of clinical intervention. It is hypothesized that hospital is often characterized by separated matters: on one hand, patient symptoms; on the other hand, emotional and organizational issues concerning healthcare workers. This paper aims to propose some intervention lines that, from specific problems, can affect the different relationships that people (patients, families or healthcare workers) experience.